2017
DOI: 10.1186/s12871-017-0330-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of remote ischemic preconditioning and control treatment for cardioprotection in sevoflurane-anesthetized CABG patients

Abstract: BackgroundRemote ischemic preconditioning (RIPC) efficacy is debated. Possibly, because propofol, which has a RIPC-inhibiting action, is used in most RIPC trials. It has been suggested that clinical efficacy is, however, present with volatile anesthesia in the absence of propofol, although this is based on one phase 1 trial only. Therefore, in the present study we further explore the relation between RIPC and cardioprotection with perioperative anesthesia restricted to sevoflurane and fentanyl, in CABG patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Sevoflurane exhibited favorable effects in animal experiments, but clinical evidence indicated no survival difference between diabetic and non-diabetic groups 11 . However, Sevoflurane preconditioning cardioprotection is undoubted in clinical applications [32][33][34] . Our study demonstrates that preconditioning can directly positively influence cell survival signaling (MAPK) in the diabetic condition, rescuing the energetic pathway independently of endogenously suppressed metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane exhibited favorable effects in animal experiments, but clinical evidence indicated no survival difference between diabetic and non-diabetic groups 11 . However, Sevoflurane preconditioning cardioprotection is undoubted in clinical applications [32][33][34] . Our study demonstrates that preconditioning can directly positively influence cell survival signaling (MAPK) in the diabetic condition, rescuing the energetic pathway independently of endogenously suppressed metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Most expert groups agree upon the fact that the impact of aging, co-morbidities and-most importantly-the drug regimen during the surgical procedure have to be addressed and clarified before implementation of RIPC into clinical practice is possible (2,21,22). In particular, for RIPC of the heart it has been shown that different anaesthetic regimens strongly influence effectivity of RIPC.…”
Section: Possible Limitations Of Translationmentioning
confidence: 99%
“…However, we did not confirm such effects in our study, further supporting the notion that intraoperative factors may have negatively affected the RIPC protective effects. Contrary to these results, Nederlof et al [ 36 ] also found no effect of RIPC on mitochondrial hexokinase or on the inflammatory mediators in atrial tissue samples of sevoflurane-anesthetized cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 80%